The Influence of Price Discount, Hedonic Shopping Motivation and Shopping Lifestyle on Impulse Buying in the Marketplace - Sarabila, Fathiya; Yunita, Yunita; Astuti, Ramlah Puji (International Journal of Business, Economics, and Social Development, 2025)
This study aims to analyze the effect of price discount, hedonic shopping motivation, and shopping lifestyle on impulse buying among students of Universitas Swadaya Gunung Jati Cirebon who shop through the Shopee marketplace. The quantitative method was used by distributing questionnaires to 250 respondents, analyzed using multiple linear regression through SPSS 25. The results showed that all three variables had a significant effect on impulse buying (R² = 0.62), with price discount as the dominant factor (β = 0.42), followed by hedonic motivation (β = 0.31), and shopping lifestyle (β = 0.25). These findings confirm that price incentives, shopping pleasure, and consumptive lifestyle play a crucial role in encouraging impulsive buying. The practical implication is that business actors are advised to optimize promotional strategies based on discounts and creative content, while academics need to explore additional variables such as FOMO or the influence of influencers. This study contributes to understanding the dynamics of digital consumer behavior in Indonesia, as well as being the basis for policy recommendations to reduce the negative impacts of impulsive shopping.